The Role of Equity Crowdfunding Business Model in Improving Employee Welfare Based on Maqashid Shari'ah Perspective: Case Study of SMEs listed in Santara Platform - Virgiawan, Rheyza; Luthfiani, Dita Sari (ITB AAS INDONESIA Surakarta, 2023)
SMEs have a big role in the country's economy. However, during the Covid-19 pandemic, the condition of SMEs declined and needed solutions, especially related to funding. Equity crowdfunding for SMEs is a breakthrough business model that has begun to be studied by many researchers. However, research on equity crowdfunding in SMEs is still rarely done. Moreover, researchers have not specifically analyzed employee welfare in the maqasid shariah perspective which is a research gap. This study aims to analyze the concept of equity crowdfunding management and its impact on employee welfare referring to the maqashid shari'ah perspective which consists of 5 aspects, namely religious protection, protection of life, protection of mind, protection of offspring and protection of property. This research is qualitative research with descriptive analysis method. The data in this study are primary and secondary data, Primary data was obtained through in-depth interviews with 5 SMEs from the food and beverage industry that had been registered at PT Santara Daya Inspiratama for the 2019-2021 period, which were randomly selected. And secondary data in this study is literature related to crowdfunding equity and maqasid shariah. This research results that the equity crowdfunding business model is a business model that overshadows the cooperation between investors and SMEs in capital. It is evident that in general crowdfunding has an important role in improving the welfare of SME employees. Specifically, from the 5 aspects of welfare based on maqasid shari'ah, it was found that there were 2 aspects that had not been achieved, namely the protection of the soul and the protection of offspring. As for the protection of religion, protection of reason and protection of property, SMEs have been able to carry out well with the encouragement of crowdfunding.